Combined Interval Training and Post-exercise Nutrition in Type 2 Diabetes: A Randomized Control Trial - Francois, Monique E.; Durrer, Cody; Pistawka, Kevin J.; Halperin, Frank A.; Chang, Courtney; Little, Jonathan P. (Frontiers in Physiology, 2017)
Background: High-intensity interval training (HIIT) can improve several aspects of cardiometabolic health. Previous studies have suggested that adaptations to exercise training can be augmented with post-exercise milk or protein consumption, but whether this nutritional strategy can impact the cardiometabolic adaptations to HIIT in type 2 diabetes is unknown. Objective: To determine if the addition of a post-exercise milk or protein beverage to a high-intensity interval training (HIIT) intervention improves cardiometabolic health in individuals with type 2 diabetes. Design: In a proof-of-concept, double-blind clinical trial 53 adults with uncomplicated type 2 diabetes were randomized to one of three nutritional beverages (500 mL skim-milk, macronutrient control or flavored water placebo) consumed after exercise (3 days/wk) during a 12 week low-volume HIIT intervention. HIIT involved 10 X 1-min high-intensity intervals separated by 1-min low-intensity recovery periods. Two sessions per week were cardio-based (at 90% of heart rate max) and one session involved resistance-based exercises (at RPE of 5-6; CR-10 scale) in the same interval pattern. Continuous glucose monitoring (CGM), glycosylated hemoglobin (HbA1c), body composition (dual-energy X-ray absorptiometry), cardiorespiratory fitness (V̇O2peak), blood pressure and endothelial function (%FMD) were measured before and after the intervention. Results: There were significant main effects of time (all p<0.05) but no difference between groups (Interaction: all p>0.71) for CGM 24-h mean glucose (-0.5 ± 1.1 mmol/L), HbA1c (-0.2 ± 0.4%), percent body fat (-0.8 ± 1.6%), and lean mass (+1.1 ± 2.8 kg). Similarly, V̇O2peak (+2.5 ± 1.6 mL/kg/min) and %FMD (+1.4 ± 1.9%) were increased, and mean arterial blood pressure reduced (-6 ± 7 mmHg), after 12 weeks of HIIT (all p<0.01) with no difference between beverage groups (Interaction: all p>0.11). Conclusion: High-intensity interval training is a potent stimulus for improving several important metabolic and cardiovascular risk factors in type 2 diabetes. The benefits of HIIT are not augmented by the addition of post-exercise protein.